Icterus Neonatorum Akibat Gangguan Metabolisme Karbohidrat Dalam Eritrosit - Abdul Salam M. Sofro Abdul Salam M. Sofro (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1980)
Neonatal jaundice is not uncommonly found in newborn infants during the first few days of life. Usually the jaundice is mild. However, in a relatively small number of cases, the jaundice would progressively increase. Hyperbilirubinemia is observed in this clinical situation.In general it may be said that hyperbilirubinemia is due either to excessive erythrocyte breakdown which results in an increase of indirect reacting bilirubin in the blood, or to the failure of conversion of indirect reacting bilirubin to the direct reacting bilirubin.It has been known that carbohydrate metabolism is the constant source of metabolic power which is required by the human red cell in order to survive in the circulation and maintain its function. Metabolic defects in the red cells may result in premature ageing of the erythrocytes and consequently hemolysis and hyperbilirubinemia occur.Key Wards: neonatal jaundice - hyperbilirubinemia - erythrocyte breakdown - indirect reacting bilirubin - direct reacting bilirubin